Impact of blanching and drying on antioxidant contents and antioxidant activity of Indian mustard leaves (Brassica juncea) - Sumitra Kumari Meena,; Mukta Agrawal, (Journal of Oilseed Brassica, 2026)
Leafy vegetables contain significant amount of bio-active health promoting compounds which act as antioxidantsthat can impart health benefits beyond basic nutrition. Blanching and dehydration by drying are processescommonly used in preservation of leafy vegetables. The present investigation was planned to study the effectof blanching and drying on antioxidant contents (total phenols, flavonoids, Vitamin C and  carotene) andantioxidant activity of mustard leaves. In the present investigation the fresh mustard leaves were collected ina lot, washed thoroughly and divided into three portions, i.e. raw, blanched and dried to know the impact ofprocessing (i.e. blanching and drying) on the antioxidant contents and antioxidant activity. Raw blanched anddried samples were analyzed for antioxidant contents and antioxidant activity through standard methods.Results of the study revealed that fresh mustard leaves contained total phenol 48.37 ± 0.45mg/100g GAE ,flavonoids 9.17 ± 0.30 mg/100g QE, vitamin C 12.65 ± 6.01 mg/100g and  carotene 6.30±0.20 mg/100g andantioxidant activity was 46.50 ± 2.90 mg/100g AAE. The antioxidant contents and antioxidant activity ofmustard leaves were found influenced by processing treatments (blanching and drying), Blanching causedloss while drying increased the concentration of antioxidant contents.